Abscisic acid, H2O2 and nitric oxide interactions mediated cold‐induced S‐adenosylmethionine synthetase in Medicago sativa subsp. falcata that confers cold tolerance through up‐regulating polyamine oxidation. Issue 5 (12th February 2014) - Guo, Zhenfei; Tan, Jiali; Zhuo, Chunliu; Wang, Congying; Xiang, Bin; Wang, Zengyu
Summary S‐adenosylmethionine synthetase (SAMS) is the key enzyme catalysing the formation of S‐adenosylmethionine (SAM), a precursor of polyamines and ethylene. To investigate the potential role of SAMS in cold tolerance, we isolated MfSAMS1 from the cold‐tolerant germplasm Medicago sativa subsp. falcata and analysed the association of SAM‐derived polyamines with cold tolerance. The expression of MfSAMS1 in leaves was greatly induced by cold, abscisic acid (ABA), H2O2 and nitric oxide (NO). Our data revealed that ABA, H2O2 and NO interactions mediated the cold‐induced MfSAMS1 expression and cold acclimation in falcata. SAM, putrescine, spermidine and spermine levels, ethylene production and polyamine oxidation were sequentially altered in response to cold, indicating that SAMS‐derived SAM is preferentially used in polyamine synthesis and homeostasis during cold acclimation. Antioxidant enzyme activities were also induced in response to cold and showed correlation with polyamine oxidation. Overexpression of MfSAMS1 in tobacco resulted in elevated SAM levels, but polyamine levels and ethylene production in the transgenic plants were not significantly changed. Compared to the wild type, transgenic plants had increased levels of apoplastic H2O2, higher transcript levels of genes involved in polyamine synthesis and oxidation, and higher activities of polyamine oxidation and antioxidant enzymes. The results showed that overexpression of MfSAMS1 promoted polyamine synthesis and oxidation, which in turn improved H2O2‐induced antioxidant protection, as a result enhanced tolerance to freezing and chilling stress in transgenic plants. This is the first report demonstrating that SAMS plays an important role in plant tolerance to cold via up‐regulating polyamine oxidation.